Evaluation of advanced multiplex short tandem repeat systems in pairwise kinship analysis. Issue 5 (September 2015) - Tamura, Tomonori; Osawa, Motoki; Ochiai, Eriko; Suzuki, Takanori; Nakamura, Takashi
Highlights The PowerPlex Fusion, GlobalFiler, and PowerPlex 21 are useful for sibship testing. The advanced systems less effectively dealt with the inference for first cousins. The advanced systems would only confer a limited advantage in parentage testing.